2003
DOI: 10.1002/tl.107
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Students for Educated Living: Virtues of Problem‐Based Learning Across the Higher Education Curriculum

Abstract: The author argues that professors must engage students in problem‐solving activities across all disciplines. To ignore students' problem‐solving skills is to undermine the possibility of creating “educated individuals” through higher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
0
17
0
4
Order By: Relevance
“…The characteristics of problem-based learning provide a unique opportunity for students to learn about themselves. As a part of the problem-solving process students must consider their own educational goals, and this is likely to require introspection about values, ethics and beliefs [32][33][34][35] Backcasting…”
Section: Strategy Description Contribution To Esdmentioning
confidence: 99%
“…The characteristics of problem-based learning provide a unique opportunity for students to learn about themselves. As a part of the problem-solving process students must consider their own educational goals, and this is likely to require introspection about values, ethics and beliefs [32][33][34][35] Backcasting…”
Section: Strategy Description Contribution To Esdmentioning
confidence: 99%
“…PBL is considered an instructional approach that engages students in problem-solving activities (Knowlton, 2003). However, Schwartz, Brophy, Lin, and Bransford (1999) warned that engagement does not guarantee desired learning outcomes.…”
Section: Processing Components Of the 3c3r Modelmentioning
confidence: 99%
“…Siemens, G. and Tittenberger, P. (2009) suggested that learning activities are experimental activities with interaction emphasising on solutions. Knowlton (2003) insisted that the Problem-Based Learning (PBL) is a pedagogy in which students learn about a subject through problem-solving activities. The learning process based on using problem-based learning.…”
Section: Introductionmentioning
confidence: 99%